Morphometry as a probe of the evolution of jellyfish galaxies: evidence of broadening in the surface brightness profiles of ram-pressure stripping candidates in the multicluster system A901/A902. Issue 1 (17th October 2020) - Roman-Oliveira, Fernanda; Chies-Santos, Ana L; Ferrari, Fabricio; Lucatelli, Geferson; Rodríguez Del Pino, Bruno
ABSTRACT: We explore the morphometric properties of a group of 73 ram-pressure stripping candidates in the A901/A902 multicluster system, at z ∼ 0.165, to characterize the morphologies and structural evolution of jellyfish galaxies. By employing a quantitative measurement of morphometric indicators with the algorithm morfometryka on Hubble Space Telescope ( F 606 W ) images of the galaxies, we present a novel morphology-based method for determining trail vectors. We study the surface brightness profiles and curvature of the candidates and compare the results obtained with two analysis packages, morfometryka and iraf/ellipse on retrieving information of the irregular structures present in the galaxies. Our morphometric analysis shows that the ram-pressure stripping candidates have peculiar concave regions in their surface brightness profiles. Therefore, these profiles are less concentrated (lower Sérsic indices) than other star-forming galaxies that do not show morphological features of ram-pressure stripping. In combination with morphometric trail vectors, this feature could both help identify galaxies undergoing ram-pressure stripping and reveal spatial variations in the star formation rate.